A qualitative study on the perspectives of the academicians regarding the profile of prospective teachers - Şahan, Gülsün; Duman, Burcu; Şahan, Gülsün; Duman, Burcu (International Symposium on New Issues in Teacher Education, 2016)
The purpose of this study to develop a profile of the prospective teachers based on opinions of the academicians working at the faculties of education. In order to do this, answers to the following questions were sought: 1) What are the social, personal and academic qualities that the academicians would like to see in prospective teachers? 2) To what extent the observed social, personal and academic qualities of the prospective teachers meet the expectations of the academicians? The study was carried out in accordance with the qualitative method. The study pattern type is case study. The study group was selected in line with easily accessible sample survey. To this end, 25 academicians working at various faculties of education throughout Turkey were interviewed. The study data were collected by semi structured interview forms. The interview questions were selected based on expert views. The data were analysed using descriptive analysis method. Based on the findings of the study, it can be suggested that the prospective teachers choose studying teaching since their university entrance exam scores match these departments, some of them do not plan being teachers in the future, the motivation of the majority of prospective teachers is low due to various reasons such as the examinations before teacher appointment and the qualifications of prospective teachers are not at the desired level since practical activities are not offered as much since syllabus is so heavy with theory lessons. Such recommendations are listed in the study as setting different criteria for selecting teacher candidates, increasing the weight of the practical activities and focusing more on cultural and artistic studies.
Keywords: Prospective teacher; Preservice education